(untitled) (The Journal of Psychology and Sociology, 2016)
The article analyzes statistical indicators of socio-economic development of the Kazakhstan regions. Tendencies of change of social structure of a modern Kazakhstan society was shown, as well as the dynamics of the main indicators of official statistics on the quality of life and material security of Kazakhstan was analyzed (poverty rate, social stratification, and others.). First type was defined, it was the indicators of consumer ability of the population and changes in income. It presents the final consumption expenditure, where there is a gradual increase in costs, as the statistics on the purchasing power of income, showing how income on consumption exceeds the cost of living. It was revealed that in the economic well-being studies deprivation analysis, limitations in social life were effective, which are feels a certain percentage of the population. Deprivation approach (or evaluation of poverty experienced by deprivation) requires consideration of a number of material, and also social indicators to determine the quality “border”. The structure of the main sources of income of the people of Kazakhstan was examined. The structure of the main sources of income can serve as another indicator of the changes in material well-be-ing of households. The main indicator of improved household well-being in Kazakhstan, both in urban and rural areas is a significant reduction in households without sources of income for 10 years. It was noted that creating a system of social development indica-tors, it should be remembered that should have the following characteristics: the integral nature of the indicators, which connects different areas and social development levels; fix the planned and actual results, not intermediate state of social development; have internal structuring nature of indicators that link the degree of development of economic and social outcomes; ability to fix not only quantitative changes, but also qualitative states.